Effect of structural transformation on the gas-sensing properties of phthalocyanine thin films - Sureeporn Uttiya (2018)
Thai Microelectronics Center, NECTEC, NST DA, 51/4, Suwingthawong Rd. Chachoengsao, 24000 Thailand We report on the use of zinc tetra-tertiary-butyl phthalocyanine (ZnTTBPc) thin films as an optical gas sensor. The ZnTTBPc films were fabricated by spin-coating onto glass substrates. The response of the ZnTTBPc films to various alcohols was monitored by using optical absorption spectroscopy under both static and dynamic conditions. The gas-sensing capability of the films was substantially improved by thermal annealing of the spin-coated films at 340 °C This procedure was found to eliminate irreversible changes in the absorption spectra after exposure to test alcohols. X-ray diffraction and atomic force microscopy measurements related this effect to the structural transformation of the ZnTTBPc films from an amorphous to a crystalline phase. The strongest gas-sensing response of the annealed films was observed for methanol. The results are in good agreement with the density functional theory (DFT) calculations, which indicate that the interaction between the Zn atom and the OH group of methanol is the strongest among the test alcohols.